2023
DOI: 10.3390/agronomy13051225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Climatic Conditions, and Agronomic Practices Used in Organic and Conventional Crop Production on Yield and Nutritional Composition Parameters in Potato, Cabbage, Lettuce and Onion; Results from the Long-Term NFSC-Trials

Abstract: Background: There is increasing evidence that the reliance on synthetic chemical pesticides and mineral fertilizers in agriculture has significant negative environmental and/or health impacts and poses a risk for future food security. Systematic reviews/meta-analyses showed that organic production systems, which omit the use of agrochemicals, produce crops with lower yields, but superior nutritional composition. However, the agronomic parameters responsible for differences in crop yields and nutritional qualit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…• greenhouse gas emissions from food production [38] Although many of the desirable impacts of specific agronomic practices shown in Figure 1 are well documented (see Table 1), Rempelos et al [3] describe that there are few studies in which the relative effects of (and interactions between) different agronomic parameters (e.g., rotation, tillage, fertilization, and crop protection) used in organic and regenerative farming were investigated. In addition, there are very few studies in which the relative importance of (and interactions between) environmental, crop genetic, and agronomic factors was investigated [3,35,[39][40][41]. However, such data are thought to be essential for the development of strategies that can mitigate the negative impacts of global climate change [18,19,37,38].…”
Section: Modeling Studymentioning
confidence: 99%
See 1 more Smart Citation
“…• greenhouse gas emissions from food production [38] Although many of the desirable impacts of specific agronomic practices shown in Figure 1 are well documented (see Table 1), Rempelos et al [3] describe that there are few studies in which the relative effects of (and interactions between) different agronomic parameters (e.g., rotation, tillage, fertilization, and crop protection) used in organic and regenerative farming were investigated. In addition, there are very few studies in which the relative importance of (and interactions between) environmental, crop genetic, and agronomic factors was investigated [3,35,[39][40][41]. However, such data are thought to be essential for the development of strategies that can mitigate the negative impacts of global climate change [18,19,37,38].…”
Section: Modeling Studymentioning
confidence: 99%
“…In contrast, older/traditional wheat species (e.g., spelt) or varieties and cultivars/populations developed and selected for the organic sectors were reported to outperform modern wheat varieties when grown in regenerative, organic farming systems [3,[39][40][41]. Similarly, the Blight-MOP, NUE-crops, and QLIF projects demonstrated that the breeding/selection of more late-blight resistant and nutrient-use-efficient cultivars should be a major target for the regenerative, low-input, and organic farming sector [3,35,[42][43][44].…”
Section: Modeling Studymentioning
confidence: 99%
“…Recent factorial field experiments and retail surveys have provided evidence that, similar to cereals, agricultural intensification (especially the use of high mineral NPK fertilizer and pesticide inputs to increase yields) can reduce the nutritional quality of fruit and vegetables [4,27,29,30,34,[68][69][70][74][75][76][77][78][79][80][87][88][89]. There is also now some evidence that excessive irrigation can have negative effects on both crop yield and quality [101].…”
Section: Agronomic Practicesmentioning
confidence: 99%
“…Foods from conventional production systems (which are based on innovations, inputs, and management practices developed/introduced during the green revolution) with foods from organic and/or traditional, extensive production systems which use (i) older and/or more resistant/robust crop and livestock genotypes and/or (ii) omit or restrict the use of many of the inputs and management practices (e.g., monoculture/short crop rotations; long indoor production periods for livestock) widely used in conventional systems [4,[23][24][25][26][27][28][29][30][31][32][33]; • Food composition data from before and after agricultural intensification [10][11][12][13];…”
mentioning
confidence: 99%
“…de Barry is still considered as one of the most harmful due to its high capacity of spreading and the fact that climatic conditions such as temperature, rainfall regimen, and air humidity favor the developmental phases of the fungus [8]. Plant and pathogen interactions are characterized by complex mechanisms and environmental conditions are considered as influential to both the condition and defense mechanisms of the plant [9][10][11][12][13]. Environmental factors also influence the pathogen's survival, considering their role in oospore germination [13,14].…”
Section: Introductionmentioning
confidence: 99%